2021
DOI: 10.1101/2021.09.01.458624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CARD8 inflammasome sensitization through DPP9 inhibition enhances NNRTI-triggered killing of HIV-1-infected cells

Abstract: Non-nucleoside reverse transcriptase inhibitors (NNRTIs) induce pyroptosis of HIV-1 infected CD4+ T cells through induction of intracellular viral protease activation, which then activates the CARD8 inflammasome. Due to high concentrations of NNRTIs being required for efficient CARD8 activation and elimination of HIV-1-infected cells, it is important to elucidate ways to sensitize the CARD8 inflammasome to NNRTI-induced activation. We show that this sensitization can be done through chemical inhibition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Some obstacles toward implementation of this strategy include the high concentrations of NNRTIs required for CARD8 inflammasome activation in HIV-1-infected cells and the fact that NNRTIs bind human serum proteins, reducing their bioavailability in vivo [74]. A recent preprint suggests that CARD8 sensitization through inhibition of DPP9, a negative regulator of CARD8, can overcome these obstacles and enhance NNRTI-triggered killing of HIV-1-infected cells [75]. Furthermore, drug screening for compounds that more efficiently trigger Gag-Pol dimerization and premature PR activation is a promising strategy to identify novel antivirals that can efficiently induce CARD8 inflammasome-dependent killing of HIV-1-infected cells with few side effects.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Some obstacles toward implementation of this strategy include the high concentrations of NNRTIs required for CARD8 inflammasome activation in HIV-1-infected cells and the fact that NNRTIs bind human serum proteins, reducing their bioavailability in vivo [74]. A recent preprint suggests that CARD8 sensitization through inhibition of DPP9, a negative regulator of CARD8, can overcome these obstacles and enhance NNRTI-triggered killing of HIV-1-infected cells [75]. Furthermore, drug screening for compounds that more efficiently trigger Gag-Pol dimerization and premature PR activation is a promising strategy to identify novel antivirals that can efficiently induce CARD8 inflammasome-dependent killing of HIV-1-infected cells with few side effects.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Based on this concept, our group recently found that DPP9 inhibition reduces the threshold concentration of NNRTIs needed to trigger pyroptosis in HIV-infected cells. [ 65 ] Another major obstacle for targeting the inflammasome for the treatment of HIV-1 infection is cytokine release during inflammasome activation. However, it is generally accepted that CD4 + T cells do not secrete the inflammatory cytokines IL-1β or IL-18.…”
Section: Targeting the Inflammasome For The Treatment Of Hiv-1 Infectionmentioning
confidence: 99%